Bankruptcy Analysis of Banking Companies in Indonesia Period 2001-2012 (Using the Altman Z-Score Model) - Andi Sanjaya; . Lindrianasari; . Aminah (International Conference On Law, Business and Governance (ICon-LBG), 2013)
The purpose of this study is to provide empirical evidence about the bankruptcy prediction model used byAltman. Research questions were constructed in this study is whether the Altman Z-Score model thatbuilt in 1968 can be used and relied upon in accommodating economic climate in Indonesia, especially asa predictor of bankruptcy in Indonesia banking company. Statistical test results showed that the AltmanZ-Score model appropriate for use in predicting the potential bankruptcy of the Indonesia bankingcompany on the observation period 2001-2012. By doing so, this study conclude that the Altman Z-Scoremodels can be a tool for predicting bankruptcy in Indonesia.